Integration of sustainable development indicators into financial reporting system - A. I. Belousov; E. V. Zakalyukina; G. V. Mihailova (Вестник Северо-Кавказского федерального университета, 2025)
Abstract. Introduction. In many cases, modern economic conditions reveal imbalance in economic, social and environmental factors, which, in fact, contradicts the concept of sustainable development, which assumes equal consideration of these components. Given the importance of environmental imperatives and their complex impact on the social and economic sphere, it is necessary to project the prerequisites for sustainable development on existing asset valuation mechanisms.Goal. The study aims to develop methods and approaches that allow the use of indicators characterizing the level of sustainable development and integrating them into modern financial reporting system.Materials and methods. Practical implementation of this approach involves the use of a balance sheet equation that allows determining capital in the form of a difference between the amount of assets and liabilities, which significantly changes the understanding of profit as an economic category.Results and discussion. Originally, the transformation of financial reporting in the direction of sustainable development can be guided by the index of adjusted net savings and the static balance theory associated with the physical form of understanding capital, which will increase its reliability and information content for various groups of users. At the same time, a strict focus on cost and price parameters, including fair value, does not reliably reflect the real volume of those benefits and values that form the basis of any sustainable development.Conclusion. A more productive solution to this problem is the simultaneous use of platforms, including digital ones, which allow simultaneously forming a system of indicators and parameters of financial and non-financial reporting while maintaining a clear focus on the interests of specific user groups.